Rooted Mediation and Culturally Responsive Teaching in a Muslim-Minority Madrasah - Muhamad Nabila Irfan; Sufyan Tsauri; Istifadah Istifadah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Faith-based schools in religious minority settings must sustain their educational identity while engaging with cultural plurality. Although culturally responsive teaching research has examined racial, ethnic, and linguistic diversity in public schools, it rarely explains how teachers in minority madrasahs negotiate religious boundaries or how their relational practices become institutionally sustainable. This study adopts Gay’s Culturally Responsive Teaching (CRT) framework and explores how teachers sustain Islamic educational commitments while engaging with local culture in a Muslim-minority setting. This study used descriptive phenomenology at an Islamic elementary school in Tabanan, Bali, Indonesia. Six teachers were the primary participants. The principal and two senior staff members provided institutional triangulation, while the parents and community perspectives supplied contextual information. The phenomenological analysis of the in-depth semi-structured interviews involved bracketing, meaning units, thematic structures, and a composite essence of the phenomenon. Five interconnected themes were identified: rooted moral presence, bounded cultural translation, context-sensitive pedagogical justice, reflective professional becoming, and movement from relational adaptation to institutional sustainability. Together, these themes constitute rooted mediation and portray teachers as rooted mediators who participate without assimilating, maintain religious distinction without hostility, and combine common academic expectations with differentiated support for students. This study extends CRT by conceptualizing boundary work as a central practice in faith-based minority education and introducing bounded cultural translation as its contextual expression. It also links teacher responsiveness to Sustainable Educational Development through the culture/pluralism pathway. The findings suggest that mentoring, collective reflection, case documentation, staff induction, and supportive leadership are needed to transform tacit individual expertise into renewable institutional capacity while preserving teachers’ judgement and religious integrity.